2021
DOI: 10.1038/s41598-021-92748-1
|View full text |Cite
|
Sign up to set email alerts
|

Swarm shedding in networks of self-propelled agents

Abstract: Understanding swarm pattern formation is of great interest because it occurs naturally in many physical and biological systems, and has artificial applications in robotics. In both natural and engineered swarms, agent communication is typically local and sparse. This is because, over a limited sensing or communication range, the number of interactions an agent has is much smaller than the total possible number. A central question for self-organizing swarms interacting through sparse networks is whether or not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This swarm theory is generally thought of in the context of real-life biological systems (e.g., insects and flocking birds) but can be applied to artificial systems as well, such as drone swarms. When the emergent effects of swarm behavior resemble the use of intelligent design, the swarm is said to exhibit swarm intelligence [15].…”
Section: Introductionmentioning
confidence: 99%
“…This swarm theory is generally thought of in the context of real-life biological systems (e.g., insects and flocking birds) but can be applied to artificial systems as well, such as drone swarms. When the emergent effects of swarm behavior resemble the use of intelligent design, the swarm is said to exhibit swarm intelligence [15].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Simulations have found that such a dense suspension of L-shaped particles exhibits a chirality-triggered oscillation phase, in which transient vortices are assembled and disassembled in a periodic manner. 34 Here it should be noted that if an attractive interaction, like the Morse potential, 22,[35][36][37][38][39] exists in a dense suspension of active spherical particles, even in the absence of a confining boundary, a stable vortex (milling) structure can be obtained. The rotational stability due to perturbation was also discussed under the assumption of such kind of milling.…”
Section: Introductionmentioning
confidence: 99%
“…Here it should be noted that if an attractive interaction, like the Morse potential, 22,35–39 exists in a dense suspension of active spherical particles, even in the absence of a confining boundary, a stable vortex (milling) structure can be obtained. The rotational stability due to perturbation was also discussed under the assumption of such kind of milling.…”
Section: Introductionmentioning
confidence: 99%